Abstract ID: 160 Advanced personalised 3D dosimetry based on Monte Carlo simulation for Peptide Receptor Radionuclide Therapy. (October 2017) - Berenato, Salvatore; Grassi, Elisa; Fioroni, Federica; Finocchiaro, Domenico; Iori, Mauro; Spezi, Emiliano
Abstract : Molecular radiotherapy (MRT) is an effective technique for the treatment of several oncological diseases, based on the delivery of radiation to malignant tissues via the interaction of an agent with molecular sites and receptors[1] . In the clinical practice, the calculation of the absorbed dose is performed using the Medical Internal Radiation Dose (MIRD) scheme, based on pre-calculated transfer functions determined on standard anthropomorphic phantoms. The MIRD scheme assumes that radiopharmaceutical activity is distributed uniformly inside the organs[2] . For this reason, dose calculation is not planned or optimised for patients' specific characteristics. To increase the efficacy and quality of clinical trials, a detailed and reliable 3D patient specific dosimetry is required. Monte Carlo techniques are shown to provide the most accurate approach for the radiotherapy dose calculation. In this work, we used Raydose Monte Carlo code[3] to provide a patient specific 3D dose distribution in MRT at the voxel level for patients enrolled as part of a clinical trial on Peptide Receptor Radiotherapy (PRRT) with 177Lu and we compared doses to lesions and OARs with standard dose calculations obtained using the MIRD method. One hundred patients were enrolled in a clinical trial in PRRT with an activity prescription of 177Lu-DOTA-Tyr3-octreotide. All patients were scanned five times with a SPECT/CT scanner and both lesions and OARs were drawn manually on fused images. Sequential scans were co-registered using a non-rigid registration algorithm. Raydose 3D dose maps were compared with dose calculations obtained using the OLINDA/EXM software. Preliminary results for the first 20 patients show that mean doses calculated with OLINDA/EXM are significantly higher than mean doses calculated with Raydose. Initial data based on Monte Carlo dose calculations suggest a possible underestimation of the dose to OARs in PRRT treatments. More accurate dose calculation could be used on a patient by patient basis to increase the prescribed activity, maintaining a safe level of toxicity. A complete analysis that includes doses to lesions is in progress.